2010
DOI: 10.1365/s10337-010-1678-7
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Determination of Simple Polyphenols in Grapes by LC Using a Monolithic Column

Abstract: The development of a rapid, reliable and reproducible LC method for the determination and quantification of 13 polyphenols (gallic acid, protocatechuic aldehyde, gentisic acid, catechin, vanillinic acid, caffeic acid, vanillin, epicatechin, syringaldehyde, p-coumaric acid, ferulic acid, sinapic acid and resveratrol) in grapes and derived products is reported. The polyphenols were separated in less than 8 min. Employed was an RP-18e (100 mm 9 4.6 mm) monolithic type column. A gradient method with the following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Because of the unsatisfactory results obtained, four slightly modified isocratic mobile phases were tested. Similarly to recent findings, we found that the presence of methanol negatively affected resolution and increased analysis time [11][12][13][14]. Thus, methanol was excluded from the mobile phase and gradients were tested using acetonitrile and acidified water.…”
Section: Optimization Of the Separationsupporting
confidence: 80%
See 2 more Smart Citations
“…Because of the unsatisfactory results obtained, four slightly modified isocratic mobile phases were tested. Similarly to recent findings, we found that the presence of methanol negatively affected resolution and increased analysis time [11][12][13][14]. Thus, methanol was excluded from the mobile phase and gradients were tested using acetonitrile and acidified water.…”
Section: Optimization Of the Separationsupporting
confidence: 80%
“…In accordance with recent findings, acetonitrile and deionized water were used as the main components of the mobile phase [3][4][5][6][7][11][12][13][14]. Successful separation requires addition of acidic additives [11].…”
Section: Optimization Of the Separationmentioning
confidence: 94%
See 1 more Smart Citation
“…spectroscopic (Andersen & Markham, 2007) or chromatographic techniques (Stefova et al, 2003;CastilloMuňoz et al, 2010;Moreno et al, 2015;Nelson et al, 2016). Reversed-phase high performance liquid chromatography (RP-HPLC) coupled to a photodiode array detector (DAD) is one of the more commonly used methods for the separation and quantification of phenolic compounds in wine (De Villiers et al, 2004;Liazid et al, 2010;Lorrain et al, 2011;Fanali et al, 2013;Favre et al, 2014;Garaguso & Nardini, 2015;Nelson et al, 2016). The use of RP-HPLC-DAD constitutes a reliable tool for the quantification of phenolic compounds by allowing maximum absorbance, controlling peak purity and identifying compounds by means of UVvisible spectra and relative retention times.…”
Section: Introductionmentioning
confidence: 99%
“…These allow higher flow-rates of eluent due to lower back-pressures without much loss of performance [20,21]. In the recent years, the preparation and application of monolithic columns have been developed rapidly in HPLC and IC [21][22][23][24][25][26]. The main forms of monoliths are organic polymer monoliths and silica-based monoliths.…”
Section: Introductionmentioning
confidence: 99%